2012
DOI: 10.1155/2012/401979
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making about the HPV Vaccine among Ethnically Diverse Parents: Implications for Health Communications

Abstract: Objective: To describe parents' knowledge, attitudes, and decision-making with regard to obtaining the HPV vaccine for their daughters. Methods: White, Black, and Hispanic parents of daughters who were age eligible to receive the HPV vaccine (9–17 years) were recruited from community settings to participate in focus groups. Parents were asked about knowledge and awareness of HPV, decision-making about HPV vaccine, as well as preferred and actual sources of HPV information. Results: Seven focus groups (n = 64 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 8 publications
(10 reference statements)
4
69
2
Order By: Relevance
“…7,64,[66][67][68][69][70] This pattern of findings is concerning given that both quantitative and qualitative studies suggested that provider recommendations were especially influential among parents from racial/ethnic minority backgrounds. 19,69,[71][72][73] Providers more often recommended HPV vaccination for patients they perceived to be at higher risk for HPV infection. Studies found that providers prioritized HPV vaccination for subpopulations including sexually active adolescents, males who might have same sex partners, and adolescents of lower socioeconomic status.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
See 4 more Smart Citations
“…7,64,[66][67][68][69][70] This pattern of findings is concerning given that both quantitative and qualitative studies suggested that provider recommendations were especially influential among parents from racial/ethnic minority backgrounds. 19,69,[71][72][73] Providers more often recommended HPV vaccination for patients they perceived to be at higher risk for HPV infection. Studies found that providers prioritized HPV vaccination for subpopulations including sexually active adolescents, males who might have same sex partners, and adolescents of lower socioeconomic status.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…4,[18][19][20]71,74,[76][77][78] However, the extent to which parents communicated about HPV vaccination beyond giving consent varied, with qualitative studies suggesting that parents from racial/ethnic minorities or with lower socioeconomic status were less likely to be engaged by providers and more likely than parents from more socially privileged backgrounds to defer to providers' advice. 19,71,73,74,77 Parents were also more likely to follow providers' advice without question when they received a strong, unambiguous recommendation. 38,74,77 Findings on adolescents' role in clinical communication about HPV vaccination were also mixed.…”
Section: Communication Rolesmentioning
confidence: 99%
See 3 more Smart Citations